2014
DOI: 10.1093/abbs/gmu092
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of <italic>Bm</italic>N cells (<italic>Bombyx mori</italic>) in response to infection with <italic>Nosema bombycis</italic>

Abstract: Nosema bombycis (N. bombycis, Nb) is an obligate intracellular parasite, which can cause pebrine disease in the silkworm. To investigate the effects of N. bombycis infection on the host cells, proteomes from BmN cells that had or had not been infected with N. bombycis at different infection stages were characterized with two-dimensional gel electrophoresis and MALDI-TOF/TOF mass spectrometry, which identified 24 differentially expressed host proteins with significant intensity differences (P < 0.05) at least a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, few studies have examined the mechanism of host response to microsporidia infection. In previous studies, many genes were found to be induced by N. bombycis that were involved in many signal transduction pathways and are therefore key components of many cellular processes [ 19 , 41 , 42 , 43 , 44 ]. Although many genes were found to be activated by N. bombycis through a genome-wide survey in our previous study [ 41 ], these genes were determined to have different levels of background expression in subsequent work [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have examined the mechanism of host response to microsporidia infection. In previous studies, many genes were found to be induced by N. bombycis that were involved in many signal transduction pathways and are therefore key components of many cellular processes [ 19 , 41 , 42 , 43 , 44 ]. Although many genes were found to be activated by N. bombycis through a genome-wide survey in our previous study [ 41 ], these genes were determined to have different levels of background expression in subsequent work [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…B. mori is an economically important insect and a lepidopteran model for investigating gene functions. In previous studies, many genes of silkworm were found to be induced by N. bombycis that were involved in many signal transduction pathways [ 19 , 41 , 42 , 43 , 44 ]. However, there was no report that UGT was induced in silkworm, and there was also few reports that UGT was involved in the process of biological stress.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody discovery in mammalian cells offers the possibility for expression in their native, full-length IgG format, thus providing access to the physiological protein folding and posttranslational modification machinery, which in comparison to microbial systems offers a superior approach to assess their drug developability parameters. 7,30 Several mammalian display platforms have been previously developed, [31][32][33][34][35][36][37][38] but due to the inherently limited throughput, none of them has achieved the widespread adoption of microbial display systems. 5 In order to overcome limitations in Cas9-driven HDR, we designed an HDR donor architecture that incorporated linearizing motifs in the backbone, similarly to what was reported before; 39 when applied to PnP cells, integration efficiencies of variable gene libraries were observed to be above 5% (Figure 1d), a 15-fold improvement over the yield of the original donor (Figure 1e).…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 obviously correlated with the proliferation activity of malignant tumor cells,20 indicating that chitin oligosaccharide plus cisplatin may be possible to inhibit the growth of tumor cells and improve the prognosis by down-regulating the expression level of Ki67. P53 gene is closely related to the tumor apoptosis and drug resistance 21. The experimental results showed that the chitin oligosaccharide plus cisplatin had no significant effect on the expression of P53 in tumor tissue.…”
Section: Discussionmentioning
confidence: 96%